Electromechanical hysteresis and relaxation processes in relaxor piezoceramics - M. G. Konstantinova; I. A. Shvetsov; N. A. Shvetsova; E. I. Petrova; A. N. Rybyanets (Journal of Advanced Dielectrics, 2025)
This paper studies the relaxation processes and electromechanical hysteresis in relaxor piezoceramics based on the PZT system. Measurements and analysis of the electric displacement and mechanical strain hysteresis loops recorded in bipolar AC electric fields in the frequency range 0.001–5[Formula: see text]Hz were performed by means of the electromechanical response characterization system (STEPHV) and program (STEP). It was found that the coercive field, remnant and saturation electric displacement, area of hysteresis loops and relative mechanical strain values are strongly dependent on frequency. As a result of this study, complete sets of parameters characterizing the switching and ferroelectric hysteresis processes in relaxor piezoceramics were obtained.